OPTIMASI KEUANGAN BERBASIS KEAMANAN: STUDI KASUS MANAJEMEN RESIKO PEMBIAYAAN DI KSPPS USB - Muarif, Ah. Dalhar (Program Studi Ekonomi Syariah, 2025)
KSPPS USB (Usaha Syariah Bersama) is a sharia cooperative founded on November 21, 2012 by alumni of the Sharia Banking Study Program, STAI Mathali'ul Falah Pati. Amidst the many cooperatives that went bankrupt in Pati Regency, KSPPS USB has been able to survive and develop well until now with assets of billions of rupiah. This study aims to examine the strategy of managing sharia-based financing at KSPPS USB, especially in optimizing security-based finance. The method used is a qualitative approach with in-depth interviews with management and direct observation of the financing operational process. The analysis uses Miles and Huberman with the stages of data collection, data reduction, data display and verification which focus on four main aspects, namely financing distribution arrangements, payment monitoring, credit risk management, and handling problematic financing. The results of the study indicate that in financing the focus is on character and capacity as the main factors, supported by a field survey process and a ranking system. This study emphasizes the importance of a combination of personal and technological approaches to improve the sustainability of institutions and the success of Islamic financing